Developmental and paleontological insights into skull bone homology and evolution - Castanhinha, Rui Alexandre Ferreira (2014)
The Gallus gallus (chicken) embryo is a central model organism in evolutionary developmental biology. Its anatomy and developmental genetics have been extensively studied and many relevant evolutionary implications have been made so far. However, important questions regarding the developmental origin of the chicken skull bones are still unresolved such that no solid homology can be established across organisms. This precludes evolutionary comparisons between this and other avian model systems in which skull anatomy has evolved significantly over the last millions of years.(...)